Psychometric properties of the French version of the climate change worry scale - Sarah Shepherd; Patrick Raynal; Myriam Guedj (Elsevier, 2024)
Introduction: As concern over climate change keeps growing, there is a need for reliable tools to assess the psychological impact of this global issue across different languages. This study presents the first French adaptation of the Climate Change Worry Scale (CCWS) and evaluates its psychometric properties. The CCWS, originally developed in English, is a 10-item self-report measure assessing personal worry about climate change. Methods: A total of 442 participants (82.1% female, mean age = 32.45, SD = 12.50) completed the CCWS along with the Climate Change Anxiety Scale (CCAS), the Penn State Worry Questionnaire (PSWQ), and the Depression Anxiety Stress Scales (DASS). Results: The CCWS showed robust internal consistency, with Cronbach's alpha and McDonald's omega values of 0.91. Convergent validity was supported by a strong correlation between the CCWS and CCAS (r = 0.79). Divergent validity was shown by weaker correlations with general worry assessed with PSWQ (r = 0.31) and symptoms of depression, anxiety, and stress measured with DASS (r = 0.24-0.30). An exploratory factor analysis supported a one-factor solution for the CCWS, explaining 51% of the variance. Factor loadings of the ten items ranged from 0.61 to 0.82. A subsequent confirmatory factor analysis confirmed an adequate fit for a reduced six-item version of the scale. Conclusions: These findings suggest that the French version of the CCWS is a reliable and valid tool for measuring climate change worry. Its strong psychometric properties make it suitable for use in French-speaking populations, enabling future cross-cultural research on climate-related psychological impacts.